Catalytic effect of Al2TiO5 on the dehydrogenation properties of LiAlH4. (29th August 2022) - Ismail, M.; Ali, N.A.; Sazelee, N.A.; Suwarno, S.
Abstract: Lithium alanate (LiAlH4 ) is considered as a promising material for storing hydrogen (H2 ) in solid-state form for onboard applications due to its advantage of high gravimetric H2 capacity. LiAlH4 could release H2 ∼7.9 wt.% when heated up to ∼250 °C. Nevertheless, the high desorption temperature, sluggish desorption kinetics, and irreversibility hamper the application of LiAlH4 for solid-state H2 storage materials. Therefore, in this study, we have used aluminum titanate (Al2 TiO5 ) as an additive to diminish the desorption temperature and enhance the desorption kinetics of LiAlH4 . The addition of a small amount of Al2 TiO5 (5 wt.%) into LiAlH4 significantly decreased the decomposition temperature and enhanced the desorption kinetics, in which Al2 TiO5 -doped LiAlH4 started to release H2 at ∼90 °C and was able to desorb H2 as much as ∼3.5 wt.% at 90 °C within 1 h. Without the catalyst, pure LiAlH4 starts to release H2 at ∼145 °C and only desorbs H2 as low as 0.3 wt.% at 90 °C within 1 h. The activation energies for H2 release in the two-step desorption process of LiAlH4 were reduced after catalysis with Al2 TiO5 . The activation energies of as-milled LiAlH4 were 80 kJ/mol and 91 kJ/mol, respectively, as calculated by the Arrhenius plot. The activation energies were lowered to 68 kJ/mol and 79 kJ/mol after milling with Al2 TiO5 . The scanning electron microscopy images revealed that the LiAlH4 particles became smaller and less agglomerated when Al2 TiO5 was added. It is believed that the in-situ formation of active species during the desorption process and reduction in particles size play a vital role in improving the dehydrogenation properties of the Al2 TiO5 -doped LiAlH4 system. Highlights: The H2 storage properties of LiAlH4 /Al2 TiO5 have been studied for the first time. The Al2 TiO5 -doped LiAlH4 composite starts to release hydrogen at ∼90 °C. The Al2 TiO5 -doped LiAlH4 composite releases 3.5 wt.% in 60 min at 90 °C. The formation of in situ AlTi phases play a catalytic role.